A COMPARATIVE ANALYSIS OF GRAMMATICAL GENDER IN ENGLISH AND MARATHI: STRUCTURE, FEATURE, FUNCTIONAL ASPECTS, AND SOCIOLINGUISTIC CONSEQUENCES - Ramchandra, Bilure Suhasini (ShodhKosh: Journal of Visual and Performing Arts, 2024)
Grammatical gender playact a pivotal role in categorise noun, regulate the structure and function of terminology worldwide based on semantic, morphological, or sometimes arbitrary measure. This composition presents a comparative analytic thinking of the grammatical gender system of rules in English and Marathi, two voice communication from the Indo-European family. While English, a West Germanic linguistic communication, has significantly deoxidize its reliance on grammatical gender, Marathi, an Indo-Aryan language, maintains a rich and intricate gender system that is deeply embedded in its grammar and ethnic identity. The field of study explore four key domain: the morphologic institution of sex, the morphologic and phonological trait specific to each lyric, the use of grammatical gender in judgment of conviction mental synthesis and meaning, and the sociolinguistic impact of gender on communicating, individuality, and cultural percept. By contrasting the simplified gender system of English with the gendered geomorphology in Marathi, the paper highlight the linguistic and cultural implications of these systems in global discourse. To support the psychoanalysis, the research incorporate visual economic aid such as charts, diagrams, and comparative tabular array, offering a clearer apprehension of sex assigning, agreement rules, and cross-linguistic remainder. This work combines theoretic exploration with practical penetration, bring home the bacon a deeper sympathy of how Grammatik gender influences language evolution and sociolinguistic moral force across different linguistic contexts.